2018
DOI: 10.2147/ijn.s156328
|View full text |Cite
|
Sign up to set email alerts
|

Targeted co-delivery of Beclin 1 siRNA and FTY720 to hepatocellular carcinoma by calcium phosphate nanoparticles for enhanced anticancer efficacy

Abstract: PurposeFTY720, known as fingolimod, is a new immunosuppressive agent with effective anticancer properties. Although it was recently confirmed that FTY720 inhibits cancer cell proliferation, FTY720 can also induce protective autophagy and reduce cytotoxicity. Blocking autophagy with Beclin 1 siRNA after treatment with FTY720 promotes apoptosis. The objective of this study was to enhance the anticancer effect of FTY720 in hepatocellular carcinoma (HCC) by targeted co-delivery of FTY720 and Beclin 1 siRNA using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
(54 reference statements)
5
9
0
Order By: Relevance
“…2 ) which is equivalent of around 1 µg/mL. This anti-cancer effect is also observed at similar dosing in other tumor preclinical models [ 17 , 75 ]. Therefore, a higher dose of Fingolimod starting from 10 mg/day might represent an interesting clinical dosing for patients with cancer, suggesting that further clinical and safety investigations might be particularly useful.…”
Section: Discussionsupporting
confidence: 63%
“…2 ) which is equivalent of around 1 µg/mL. This anti-cancer effect is also observed at similar dosing in other tumor preclinical models [ 17 , 75 ]. Therefore, a higher dose of Fingolimod starting from 10 mg/day might represent an interesting clinical dosing for patients with cancer, suggesting that further clinical and safety investigations might be particularly useful.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, miR-216a enhances the radiosensitivity of pancreatic cancer cells by suppressing Beclin 1-mediated autophagy (35). The combined delivery of Beclin 1 siRNA and FTY720 (a novel immunosuppressive agent with effective anticancer properties) more efficiently inhibits liver cancer cell progression by suppressing protective autophagy and increasing apoptosis (36), which is consistent with the results of the present study. The present study found that Beclin 1 inhibited p53, Bax, and cleaved caspase-3 expression in starved HepG2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…This review concluded that there are some new strategies available such as ligand mediated active targeting, nano carrier based RES uptake and some molecular conjugates of targeting ligands and active drugs that applicable to target effectively and killed the actively proliferating cancer cells, 68,69 and the available targeting ligands such as asialoglycoprotein, lactose and mannose, liver cancer cell specific antibodies, aptamers, avimers, bile acid conjugation, Collagen Type VI Receptor, Collagen Type VI Receptor and others ligands were successfully used for targeting liver cancer and further can be used for targeting and deliver anticancer drug or drug which are used to treatment of liver diseases. 70…”
Section: Resultsmentioning
confidence: 99%